DISEASE CONTROL PLAN: READING COMMUNICABLE ILLNESS IN THE ṢAḤĪḤ AL-BUKHĀRĪ - Sapiee, Muhammad Lutfi (International Prophetic Conference (SWAN) FPQS USIM, 2022)
The World Health Organization (WHO) has outlined 11 indicators in their 2021 Strategic Preparation and Response Plan (SPRP) to combat the pandemic. Since the year 2020, Covid 19 has been observed. Hadith of the Prophet Muhammad (PBUH) found in kitāb al-mardhā and kitāb al-ṭibb of Ṣaḥīḥ al-Bukhārī showcase approaches and principles of modern epidemiology-based solutions. This is shown in comparison to Islamic tradition. Delve deeper into the setting of communicable illness in Ṣaḥīḥ Bukhārī; we found that although the epidemiology study as a different set of knowledge yet to exist in the time of the prophet, the general guidelines provided by the prophetic revelation stand through the test of time proving that this is not indeed the mundane human talking instead it is indeed the divine guidance. When we talk about disease control plan, moving to the modern-day phase of epidemiology, although the initial plan was laid out by Prophet Muhammad (peace be upon him) in various ḥadīth, this paper also benefits the source from the World Health Organization (WHO) in the form of a document named Strategic preparedness and response plan (SPRP). This response plan contains some of the most critical mechanisms to combat COVID 19 on a global scale. As the title suggests, this paper also attempted to build a sort of disease control plan with two unified sources as an effort to minimalize the gap that exists between Islamic knowledge and so-called worldly science wisdom.